Resultados da escavação da Mamoa D’Alagoa (Toubres - Jou) - Murça (Trás-os-Montes) - Sanches, Maria de Jesus; Nunes, Susana Andreia (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
Results from excavation work carried out at Mamoa d’Alagoa (Trás-os-Montes, North-eastern Portugal) in 2000-2001, are presented here. This is a megalithic monument, with chamber and other access structures - megalithic corridor, corridor opened directly in the clayey sediments, antechamber – in connexion with a covering sub-circular mound. Special emphasis is given to the different phases of construction / use / “closure” during the first half of the 4th millennium BC. The intentional and constant use of fire is also pointed out. This may have a ritual significance.